Shifting to renewal energy : consumer perception on large household purchases - Sood, Vishaal (2021)
The research studies the energy consumption of consumers by examining large household purchases. The research on consumer attitudes towards energy consumption and thus on large household purchases are relevant in modern days. Perceived ease of use and perceived behaviour influence is examined in consumer behaviour. The research methodology was a qualitative study, and the result was analysed using SPSS statistical method. The data was collected in April -June 2020 in the Northern Periphery and the Arctic area. The results indicate that consumer perceived behaviour and ease of use play an important role in purchasing large household purchases. Consumers attitudes and habits refine intentions to implementation. This thesis suggests that risks and total costs are the main factors influencing large household purchases. However, governmental incentives have been shown to influence household consumption. The result tells that large household purchases are positively influenced behavioural intentions. Consumer’s perception of ease of use and usefulness using large household products positively impacts behavioural intention for ongoing use of that product. Tutkimus tutkii kuluttajien energiankulutusta tutkimalla suuria kotitaloushankintoja. Tutkimus kuluttajien asenteista energiankulutukseen ja siten kotitalouksien suuriin ostoihin on ajankohtainen. Kuluttajien käyttäytymisessä tarkastellaan helppokäyttöisyyttä ja käyttäytymisen vaikutusta. Tutkimusmenetelmä oli laadullinen tutkimus, ja tulos analysoitiin SPSS-tilastollisella menetelmällä. Tiedot kerättiin huhtikuusta kesäkuuhun 2020 pohjoisella periferialla ja arktisella alueella. Tulokset osoittavat, että kuluttajien havaitsemalla käytöksellä ja helppokäyttöisyydellä on tärkeä rooli suurten kotitalousostojen ostamisessa. Kuluttajien asenteet ja tavat tarkentavat aikeita toteuttaa. Tämä opinnäytetyö viittaa siihen, että riskit ja kokonaiskustannukset ovat tärkeimmät tekijät, jotka vaikuttavat suuriin kotitalouksien ostoihin. Valtion kannustimien on kuitenkin ...